Analisis Pengaruh Jumlah Penduduk, Indeks Pembangunan Manusia dan Upah Minimum Terhadap Pengangguran di Kabupaten Bangkalan - Indah Mei Pratiwi; Marseto Marseto; Sishadiyati Sishadiyati (CV. Syntax Corporation Indonesia, 2021)
Unemployment is one of the problems that has not been resolved until now. Bangkalan Regency is part of the Province of East Java, which is on the western tip of Madura Island and still has a high unemployment rate. This study aims to determine the effect of Total Population, Human Development Index and Minimum Wage on Unemployment in Bangkalan Regency 2005-2019. This study uses secondary data from 2015-2019 with multiple linear regression analysis using the SPSS program. By knowing this situation, it is hoped that the regional government of Bankala Regency will be able to open new jobs to reduce the existing unemployment rate. Based on the results of this study, it shows that the Total Population and Human Development Index variables show a negative direction and have a significant effect on the unemployment variable. Meanwhile, the Minimum Wage variable shows a positive direction and has a significant effect. Together, the three independent variables have an effect on the unemployment variable in Bangkalan Regency in 2005-2019